Deviations from the diffusion tensor model as revealed by contour plot visualization using high angular resolution diffusion-weighted imaging (HARDI) - Hirsch, Jochen; Schwenk, Stefanie M.; Roßmanith, Christina; Hennerici, Michael G.; Gass, Achim (Magnetic resonance materials in physics, biology and medicine, 2003)
The standard diffusion tensor model is limited in its ability to provide detailed information about multidirectional fiber architecture in human white matter. Additional directional acquisition of diffusivity properties with high angular resolution diffusion-weighted imaging (HARDI) acquisition schemes may deliver more information on areas with fiber crossings than standard DTI. However, representation of the additional information and the rating and visualization of fiber complexity is challenging. We used projection 2D-plots in combination with a HARDI acquisition scheme of 129 diffusion directions and compared the spherical diffusion variance index (SDI) with the relative anisotropy index (RAI). In normal controls, white matter areas with unidirectional fiber arrangement and areas with more complex fiber composition were identified with this approach. HARDI confirms and can visualize deviations from the tensor-like representation, thereby providing information on fiber structure complexity, which may be of considerable interest for clinical studies.